Enhancing Job Performance through Specialized Training: The Role of Job Satisfaction and Motivation in College and University Office Worker - Ullah, Naqeeb; Asghar, Umair (2024)
The effectiveness with which an organization utilizes its human resources is a key determinant of its overall performance. Specialized training programs play a crucial role in enhancing employees' skills and developing new competencies. This study investigates the impact of training on job performance among office workers in college and university settings, with a particular emphasis on how job satisfaction and motivation influence this relationship. The research utilizes secondary data and a structured questionnaire, analyzing responses from a sample of 150 office workers through SPSS analysis software. The study finds a significant positive correlation between training and job performance, indicating that well-designed training programs contribute to improved employee achievement. Furthermore, the study explores how job satisfaction and motivation mediate the relationship between training and performance. The results reveal that both job satisfaction and motivation play critical roles in understanding the effects of training on job performance. The findings highlight the importance of not only implementing effective training programs but also addressing factors that enhance job satisfaction and motivation. Organizations should focus on creating training programs that are tailored to employees' needs while also fostering a work environment that supports job satisfaction and motivation. This dual approach is essential for maximizing the benefits of training and improving overall job performance. The study provides valuable insights for managers and policymakers aiming to design and implement training initiatives that drive performance and employee satisfaction.